Performing research : four contributions to HCI - Taylor, Robyn; Spence, Jocelyn; Walker, Brendan; Nissen, Bettina; Wright, Peter (2017)
This paper identifies a body of HCI research wherein the researchers take part in digitally mediated creative experiences alongside participants. We present our definition and rationale for ‘self-situated performance research’ based on theories in both the HCI and performance literatures. We then analyse four case studies of this type of work, ranging from overtly ‘performative’ staged events to locative audio and public making. We argue that by interrogating experience from within the context of self-situated performance, the ‘performer/researcher’ extends traditional practices in HCI in the following four ways: developing an intimate relationship between researchers and participants, providing new means of making sense of interactions, shaping participants’ relationship to the research, and enabling researchers to refine their work as it is being conducted.